Decision-Making for Surgery in the Management of Patients with Univentricular Heart - Davies, Ryan Robert; Pizarro, Christian (Frontiers in Pediatrics, 2015)
A series of technical refinements over the past thirty years, in combination with advances in perioperative management, have resulted in dramatic improvements in the survival of patients with univentricular heart. While the goal of single ventricle palliation remains unchanged—normalization of the pressure and volume loads on the systemic ventricle, the strategies to achieve that goal have become more diverse. Optimal palliation relies on a thorough understanding of the changing physiology over the first years of life and the risks and consequences of each palliative strategy. This review describes how to optimize surgical decision-making in univentricular patients based on a current understanding of anatomy, physiology, and surgical palliation.